Methodology to determine service delivery levels for public transportation. Issue 2 (17th February 2016) - Das, Shreya; Pandit, Debapratim
ABSTRACT: When designing transit services, the Level-of-Service concept has been widely used by transport planners and service providers to assess the service quality of an existing transit system. In addition to the service quality assessment, service providers also need to estimate the service levels that will satisfy a maximum number of users and potential users, across all socio-economic groups, so as to maximize patronage. This paper demonstrates a method using the concept of 'user satisfaction levels' and their 'zone of tolerance', along with total utility and marginal utility for service providers, to provide a range of service delivery levels for individual transit service attributes in the city of Kolkata. This range of service levels provides a guideline for service providers within which they can consider making an improvement in service level. However, the final decision on service improvement is an outcome of both financial and infrastructural feasibility.